Self-heating early-strength tailing-based geopolymer

By mechanically activating high calcium tailings, sodium hydroxide, and high-active lime, and combining with geopolymer additives, a premature-strength geopolymer is prepared, which solves the construction problems of heating and curing in the prior art, and achieves the dual goals of high strength and economic benefits.

CN119822666AActive Publication Date: 2025-04-15CCFEB CIVIL ENG
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202510327599.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

In the prior art, when preparing ground polymer with tailings, heating equipment is required to heat and cure the ground polymer, which requires strict construction conditions and is difficult to achieve room temperature curing and early strength improvement.

Method used

High calcium tailings, sodium hydroxide and high active lime are used to mechanically activate, to enhance the reactivity of high calcium tailings, and to form a slurry for molding and curing through the combination of geopolymer precursor powder A and geopolymer additive B, a slurry is formed and cured, so as to realize the preparation of self-heating premature strength geopolymer.

Benefits of technology

It significantly improves the strength of the geopolymer and realizes the early-stress self-heating and early-strength geopolymer with high early strength. It does not require external heating and curing, has simple process, and can absorb tailings on site, which has good economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822666A_ABST
    Figure CN119822666A_ABST
Patent Text Reader

Abstract

The invention relates to a self-heating early-strength tailing-based geopolymer, which is obtained by molding and curing slurry formed by mixing geopolymer precursor powder A and a geopolymer auxiliary agent B with water or without water, the geopolymer precursor powder A comprises the following raw materials: high-calcium tailings, sodium hydroxide, high-activity lime and fly ash; before the raw materials of the geopolymer precursor powder A are mixed, the raw materials including the high-calcium tailings, the sodium hydroxide and the high-activity lime are mechanically activated; and the geopolymer auxiliary agent B comprises the following raw materials: a water reducing agent, a thermal insulation material and water glass. The strength of the geopolymer is remarkably improved, the early strength is high, external heating curing is not needed, the preparation process and the construction method are simple, tailings can be consumed on site, cement with the same strength can be replaced to serve as a building roadbed material and the like, and good economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials and solid waste resource utilization, and in particular to a self-heating early-strength geopolymer for absorbing tailings. Background Art

[0002] After the ore is processed, a large amount of tailings will be generated. As the grade of the mineable ore continues to decrease, the amount of tailings generated each year is also increasing year by year. Tailings are waste generated after the ore has gone through the beneficiation or smelting process, which contains unextracted minerals and a large amount of impurities, such as metal elements, mineral particles, chemicals, etc. At present, the utilization rate of tailings in my country is only about 30%, and the remaining large amount of tailings is stored in the tailings pond. The large amount of tailings accumulation not only wastes precious land resources, but also brings serious pollution and safety hazards to the environment. The resource utilization of tailings not only helps to reduce the harm of tailings to the environment, but also realizes the efficient reuse of waste and reduces the pressure on limited natural resources.

[0003] Geopolymer is a type of inorganic polymer structural cementitious material formed by silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron. It was first developed by French Professor J. Davidovits in the late 1970s. Compared with traditional silicate building materials, geopolymer has the following advantages: (1) Environmental advantage: Compared with the high-temperature calcination in the cement manufacturing process, its carbon emissions are relatively small; (2) Crack resistance: Geopolymer can reduce the occurrence of cracks on the surface of buildings due to its nano-scale microstructure and excellent toughness; (3) Corrosion resistance: It can slow down the erosion of building materials by chemicals and enhance the durability of building materials; (4) Thermal performance advantage: Geopolymer can maintain good stability in high temperature environment and can provide excellent thermal insulation performance in some composite materials, reducing the energy consumption of buildings. In short, geopolymer has more advantages in environmental protection, physical properties, chemical properties, thermal properties and flexibility than traditional cement building materials, providing more innovative possibilities for the construction field and promoting the sustainable development of the construction industry.

[0004] Patent CN104844081A discloses a concrete with granite powder as the main mineral admixture. However, in the patent, the granite powder is only used as aggregate and does not participate in the reaction. The admixture amount is only 5-17.5wt%. There are problems such as low powder utilization rate, low product compressive strength and low added value.

[0005] Although patents CN113735473A and CN113620618A have partially solved the technical problem that solid waste can only be used as a small amount of filler, high-temperature roasting and a variety of complex reagents must be used to achieve the leaching of active silicon and aluminum. In addition, the product preparation process is complicated, the overall compressive strength is low, and the high-temperature roasting cost is high and does not conform to the development trend of green and low-carbon, making it difficult to promote and apply on a large scale.

[0006] CN115849781A discloses a geopolymer based on multiple solid wastes and a preparation method thereof. Granite powder, silica fume and lime are mixed and ground and then mixed evenly with fine-grained fly ash. The obtained precursor powder is mixed evenly with an alkali activator to obtain a slurry; then the slurry is formed and cured to obtain a geopolymer. Although this method does not require alkali thermal activation of solid waste granite powder, it only increases the specific surface area of ​​the stone powder particles by grinding, providing favorable conditions for the attachment of silica fume, thereby providing favorable conditions for the formation of later silicon-rich gel. It does not essentially change the crystallinity of the tailings to fully stimulate the silicon-aluminum activity in the tailings. Moreover, since the tailings geopolymer needs to be sealed, heated and cured to ensure a certain compressive strength, it cannot be consumed on site when the tailings are treated on site. The preparation method is cumbersome and costly, which is not conducive to later industrial applications.

[0007] It can be seen that in the existing technology, when preparing geopolymers by using tailings in actual construction, heating equipment is required to heat and solidify the geopolymers, which places strict requirements on construction conditions and is difficult to achieve. Therefore, it is urgent to develop a method for preparing geopolymers by curing tailings at room temperature and improving the early strength of geopolymers. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the above-mentioned defects in the prior art and provide a self-heating early-strength tailings-based polymer with high early strength.

[0009] The technical solution adopted by the present invention to solve the technical problem is as follows: a self-heating early-strength tailings-based polymer, which is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with or without water; The raw materials of the geopolymer precursor powder A include high calcium tailings, sodium hydroxide, high active lime and fly ash; before mixing the raw materials of the geopolymer precursor powder A, the raw materials including the high calcium tailings, sodium hydroxide and high active lime are mechanically activated together; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to high active lime is 10-110:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to sodium hydroxide is 20-110:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is less than 4.5:1; In the slurry, the mass ratio of the geopolymer precursor powder A to the geopolymer additive B is 1-100:1; The water content of the slurry is below 40 wt %.

[0010] Preferably, the mechanical force activation adopts high-energy ball milling.

[0011] Preferably, the water reducing agent is one or more of polycarboxylic acids, lignin sulfonates, and aminosulfonic acids.

[0012] Preferably, the thermal insulation material is one or more of polystyrene particles, glass beads, and composite silicates.

[0013] Preferably, the water content of the water glass is 50 wt%~60 wt%.

[0014] More preferably, the rotation speed of the high energy ball milling method is 200 rpm or more.

[0015] More preferably, the processing time of the high energy ball milling method is 5 minutes or more.

[0016] Preferably, the components of the high-calcium tailings include: CaO 15 wt%~30 wt%, SiO2 20 wt%~50 wt%, Al2O3 5 wt%~10 wt%.

[0017] Preferably, the digestion temperature of the high-activity lime is above 90° C., and the digestion time is above 30 minutes.

[0018] Preferably, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to high active lime is 20-100:1.

[0019] Preferably, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to sodium hydroxide is 30-100:1.

[0020] Preferably, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is less than 4:1.

[0021] Preferably, the components of the fly ash include: SiO2 35 wt%~50 wt%, Al2O3 15 wt%~ 35wt%, and CaO2 wt%~10 wt%.

[0022] Preferably, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is 0.8-3:1.

[0023] Preferably, in the geopolymer additive B, the mass ratio of the water reducing agent to the thermal insulation material is 1-10:1.

[0024] Preferably, in the geopolymer additive B, the mass ratio of the water reducer to the water glass is 0.1-0.4:1.

[0025] Preferably, in the slurry, the mass ratio of the geopolymer precursor powder A to the geopolymer additive B is 2-60:1.

[0026] Preferably, the water content of the slurry is 10 wt%~30 wt%.

[0027] Preferably, the curing time of the slurry is 4 to 72 hours.

[0028] The present invention has the following beneficial effects: (1) The strength of the geopolymer is significantly improved: the present invention innovatively uses high-calcium tailings, sodium hydroxide, and highly active lime to perform mechanical activation together, thereby enhancing the reactivity of the high-calcium tailings, making the high-calcium tailings have alkali-activated activity, and further forming a gel phase, thereby significantly improving the strength of the geopolymer; (2) The CSH and NASH gel phases in the geopolymer work synergistically to significantly improve the strength of the geopolymer; (3) The geopolymer has high early strength, does not require external heating for curing, has simple preparation process and construction method, can dispose of tailings on site, can replace cement of the same strength as a construction roadbed material, etc., and has good economic benefits.

[0029] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 The X-ray diffraction diagrams of the high calcium tailings after mechanical activation in Examples 1 and 2 of the present invention and the high calcium tailings after ordinary ball milling in Comparative Example 1; Figure 2 It is a graph showing the infrared spectrum detection results of the geopolymers obtained in Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0031] In order to make the purpose, scheme and beneficial technology of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be pointed out that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0032] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0033] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and the “multiple” in “one or more” means two or more, and the “multiple” in “one or more” means two or more.

[0034] The embodiment of the present invention provides a self-heating early-strength tailings-based polymer, which is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with or without water; The raw materials of the geopolymer precursor powder A include high calcium tailings, sodium hydroxide, high active lime and fly ash; before mixing the raw materials of the geopolymer precursor powder A, the raw materials including the high calcium tailings, sodium hydroxide and high active lime are mechanically activated together; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to high active lime is 10-110:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to sodium hydroxide is 20-110:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is less than 4.5:1; In the slurry, the mass ratio of the geopolymer precursor powder A to the geopolymer additive B is 1-100:1; The water content of the slurry is below 40 wt %.

[0035] High calcium tailings often come from iron tailings, lead-zinc tailings, tungsten tailings, etc.; the silicon, aluminum and calcium components in high calcium tailings are mainly present in inert minerals such as quartz, mica and zeolite, and do not have alkali excitation activity, which greatly limits its application as a geopolymer raw material. In the embodiment of the present invention, high calcium tailings, sodium hydroxide and high-activity lime are mechanically activated together, which can make the three mixed more uniformly, thereby prompting the high-activity lime to provide reaction heat uniformly; after grinding, the high-activity lime can more easily react with the active ingredients in sodium hydroxide and high calcium tailings to form a stronger gelling material. This helps to improve the strength and stability of geopolymers. Sodium hydroxide can provide a strong alkaline environment during the activation process, and can react chemically with the components in the tailings (such as silicon, aluminum, and calcium compounds). Under high pH conditions, these components are more easily dissolved and recrystallized. Mechanical force activation applies high-frequency impact, shear and friction to the particles, which can destroy the crystal structure of the tailings, increase lattice defects and broken bonds, and even convert some crystalline substances into more reactive amorphous states. Under the synergistic effect of mechanical force activation and sodium hydroxide, the stable crystalline structure in the tailings may be destroyed and partially converted into an amorphous state, so that the originally stable substance becomes a thermodynamically unstable but more reactive state. The silicon-aluminum-calcium components in the high-calcium tailings have alkali-activated activity after mechanical force activation of the present invention. The active silicon-calcium can promote the formation of the CSH gel phase, and the active silicon-aluminum-calcium can promote the formation of the NASH gel phase. Under the interweaving effect of the two gel networks, the strength of the geopolymer can be significantly improved.

[0036] The synergistic effect of the heat release of high-activity lime hydration, the heat release of sodium hydroxide dissolution, and the insulation material blocking heat loss enhances the early strength of the geopolymer. The heat released by lime hydration is conducive to the continued progress of the geopolymerization reaction and the hydration reaction, accelerates the formation of gel phases such as CSH and NASH, and improves the early strength of the geopolymer gel material. However, it is difficult to meet the heat demand of the self-heating early-strength geopolymer by only using the heat release of lime hydration. The present invention releases a large amount of heat by hydrating high-activity lime with high digestion temperature and long digestion time, and the dissolution of sodium hydroxide will further release a large amount of heat to meet the temperature demand of the self-heating early-strength geopolymer. At the same time, the insulation material in the insulation suspension can slow down the internal heat loss to the outside, reduce the temperature exchange inside and outside the geopolymer, thereby delaying the heat loss and further improving the early strength of the geopolymer gel material. The synergistic effect of the three of high-activity lime, sodium hydroxide and insulation material can realize the solidification of geopolymer without external heating, and the on-site construction and disposal of tailings.

[0037] Water glass is both an alkali activator and a silicon source in geopolymers. As an alkali activator, water glass promotes the dissolution of aluminosilicate raw materials to form geopolymer gel; the silicate in water glass provides a silicon source for the geopolymer reaction, combines with aluminate to form aluminosilicate gel, and enhances the strength of the material.

[0038] On the one hand, water reducers disperse particles and reduce friction between particles, thereby improving the fluidity and workability of geopolymer slurry, making it easier to pour and form. On the other hand, water reducers help form a denser structure and enhance the compressive and flexural strength of geopolymers.

[0039] The self-heating early-strength tailings-based polymer provided by the embodiment of the present invention has the following advantages: (1) The strength of the geopolymer is significantly improved: the present invention innovatively uses high-calcium tailings, sodium hydroxide, and highly active lime to perform mechanical activation together, thereby enhancing the reactivity of the high-calcium tailings, making the high-calcium tailings have alkali-activated activity, and further forming a gel phase, thereby significantly improving the strength of the geopolymer; (2) The CSH and NASH gel phases in the geopolymer work synergistically to significantly improve the strength of the geopolymer; (3) The geopolymer has high early strength, does not require external heating for curing, has simple preparation process and construction method, can dispose of tailings on site, can replace cement of the same strength as a construction roadbed material, etc., and has good economic benefits.

[0040] In an embodiment of the present invention, the mechanical force activation adopts a high-energy ball milling method. Common high-energy ball mills on the market can be used, such as planetary, stirring and vibration high-energy ball mills. Compared with ordinary ball mills, high-energy ball mills can achieve higher rotation speeds and stronger impact forces, making the collision between the grinding medium and the material more intense, and applying a large amount of mechanical energy in a short time.

[0041] In an embodiment of the present invention, the water reducing agent is one or more of polycarboxylic acids, lignin sulfonates, and aminosulfonic acids.

[0042] In an embodiment of the present invention, the thermal insulation material is one or more of polystyrene particles, glass beads, and composite silicates.

[0043] In an embodiment of the present invention, the water content of the water glass is 50 wt%~60 wt%.

[0044] In some embodiments of the present invention, the rotation speed of the high energy ball milling method is above 200 rpm. High energy ball milling requires a relatively high rotation speed. If the rotation speed is too low, it can hardly be called high energy ball milling even if a high energy ball mill is used.

[0045] In some embodiments of the present invention, the processing time of the high energy ball milling method is more than 5 minutes.

[0046] In some embodiments of the present invention, the rotation speed of the high-energy ball milling method is 200~1000rpm. Experimental results show that when the rotation speed is too low, the effect will be similar to that of ordinary ball milling, and it is difficult to promote phase change or amorphization on the surface of the tailings, and it is impossible to stimulate the activity of silicon-aluminum-calcium minerals in the high-calcium tailings themselves, and it is also impossible to achieve mechanical activation. The rotation speed is higher than this range and can still achieve phase change or amorphization on the surface of the tailings, and stimulate the activity of silicon-aluminum-calcium minerals in the high-calcium tailings themselves, but too high a ball milling speed will require higher energy, resulting in excessively high costs and waste of resources.

[0047] In some embodiments of the present invention, the high-energy ball milling treatment time is 5 to 60 minutes. Longer high-energy ball milling treatment can still achieve phase change or amorphization on the tailings surface, and stimulate the activity of silicon-aluminum-calcium minerals in the high-calcium tailings themselves. However, it is unnecessary to continue the high-energy ball milling treatment after the reaction is basically completed, which will also cause a waste of resources.

[0048] In an embodiment of the present invention, the components of the high-calcium tailings include: CaO 15 wt%~30 wt%, SiO2 20wt%~50 wt%, Al2O3 5 wt%~10 wt%.

[0049] Highly active lime is a common term in the industry. The activity is an indicator of the reaction speed of quicklime and is one of the important criteria for testing the quality of quicklime. In an embodiment of the present invention, the digestion temperature of the highly active lime is above 90°C and the digestion time is above 30 minutes.

[0050] In an embodiment of the present invention, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to high active lime is 20-100:1.

[0051] In an embodiment of the present invention, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to sodium hydroxide is 30-100:1.

[0052] In an embodiment of the present invention, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is less than 4:1.

[0053] In an embodiment of the present invention, the fly ash comprises: SiO2 35 wt%~50 wt%, Al2O3 15wt%~35wt%, and CaO 2 wt%~10 wt%.

[0054] In an embodiment of the present invention, in the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is 0.8-3:1.

[0055] In some embodiments of the present invention, grinding and mixing are used when mixing the raw materials of the geopolymer precursor powder A; commonly used grinding and mixing methods can be used, such as general ball milling mixing.

[0056] In an embodiment of the present invention, in the geopolymer additive B, the mass ratio of the water reducing agent to the thermal insulation material is 1-10:1.

[0057] In an embodiment of the present invention, in the geopolymer additive B, the mass ratio of the water reducer to the water glass is 0.1-0.4:1.

[0058] In an embodiment of the present invention, in the slurry, the mass ratio of the geopolymer precursor powder A to the geopolymer additive B is 2-60:1.

[0059] In an embodiment of the present invention, the water content of the slurry is 10 wt%~30 wt%.

[0060] In some embodiments of the present invention, the slurry is injected into a mold for molding.

[0061] In some embodiments of the present invention, after the slurry is injected into a mold for forming, it is covered with a film for solidification, and after demoulding, it is cured to obtain a formed self-heating early-strength tailings-based polymer.

[0062] In an embodiment of the present invention, the curing time of the slurry is 4 to 72 hours. The curing of the slurry can be carried out at room temperature without external heating.

[0063] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations will be made within the scope of the disclosure of the present invention. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight. Unless otherwise stated, all reagents used in the examples are available through conventional commercial sources or are synthesized according to conventional methods and can be used directly without further processing. Unless otherwise stated, the instruments used in the examples are available through conventional commercial sources.

[0064] The water reducer used in each embodiment and comparative example was purchased from Jiangsu Subote New Materials Co., Ltd.; the thermal insulation materials were purchased from Hebei Shengda Insulation Building Materials Co., Ltd.; the water glass was purchased from Wuxi Yatai United Chemical Co., Ltd.; the high-calcium tailings were taken from the tailings ponds in Ezhou, Hubei and Handan, Hebei; the high-activity lime was purchased from Hunan Hengyang Hengxin Environmental Protection Co., Ltd.; and the fly ash was purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0065] The 7-day compressive strength test performed in each embodiment and comparative example adopts the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T 5008-2019).

[0066] For the convenience of comparison, the strength test results of various embodiments and comparative examples are summarized in Table 1.

[0067] Example 1 The self-heating early-strength tailings-based polymer of this embodiment is obtained by forming and curing a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 40:1, and the water content of the mixed slurry is 20 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 100 parts of high-calcium tailings, 2 parts of sodium hydroxide, 5 parts of high-activity lime and 100 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy planetary ball mill, a rotation speed of 500 rpm, and a processing time of 20 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 3:1; the mass ratio of the water reducing agent to the water glass is 0.4:1.

[0068] The water reducing agent used in this embodiment is a polycarboxylic acid water reducing agent.

[0069] The thermal insulation material used in this embodiment is polystyrene particles.

[0070] The components of the high calcium tailings used in this embodiment include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt% The digestion temperature of the high-activity lime used in this embodiment is 90° C. and the digestion time is 60 min.

[0071] The components of the fly ash used in this embodiment include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0072] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 24 hours. After demolding, it is cured at room temperature to finally obtain a formed self-heating early-strength tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 47.25 MPa.

[0073] Example 2 The self-heating early-strength tailings-based polymer of this embodiment is obtained by forming and curing a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 10 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 100 parts of high-calcium tailings, 2 parts of sodium hydroxide, 2.5 parts of high-activity lime and 50 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 600 rpm and a processing time of 30 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 5:1; the mass ratio of the water reducing agent to the water glass is 0.1:1.

[0074] The water reducing agent used in this embodiment is a lignin sulfonate water reducing agent.

[0075] The thermal insulation material used in this embodiment is vitrified microspheres.

[0076] The components of the high calcium tailings used in this embodiment include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0077] The digestion temperature of the high-activity lime used in this embodiment is 100° C. and the digestion time is 50 min.

[0078] The components of the fly ash used in this embodiment include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0079] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 48 hours. After demolding, it is cured at room temperature to finally obtain a formed self-heating early-strength tailings geopolymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 54.9MPa.

[0080] Example 3 The self-heating early-strength tailings-based polymer of this embodiment is obtained by forming and curing a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 50:1, and the water content of the mixed slurry is 30 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 1 part of sodium hydroxide, 1 part of high-activity lime and 40 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy planetary ball mill with a rotation speed of 800 rpm and a processing time of 20 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 3:1; the mass ratio of the water reducing agent to the water glass is 0.3:1.

[0081] The water reducing agent used in this embodiment is a polycarboxylic acid water reducing agent.

[0082] The thermal insulation material used in this embodiment is composite silicate.

[0083] The components of the high calcium tailings used in this embodiment include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0084] The digestion temperature of the high-activity lime used in this embodiment is 120° C. and the digestion time is 30 min.

[0085] The components of the fly ash used in this embodiment include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0086] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 40 hours, and then demolded and cured at room temperature to finally obtain a formed self-heating early-strength tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 57.5MPa.

[0087] Example 4 The self-heating early-strength tailings-based polymer of this embodiment is obtained by forming and curing a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 15 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 2 parts of sodium hydroxide, 3 parts of high-activity lime and 20 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 200 rpm and a processing time of 60 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 1:1; the mass ratio of the water reducing agent to the water glass is 0.2:1.

[0088] The water reducing agent used in this embodiment is an aminosulfonic acid water reducing agent.

[0089] The thermal insulation material used in this embodiment is composite silicate.

[0090] The components of the high calcium tailings used in this embodiment include: CaO 15.22 wt %, SiO2 20.18 wt %, Al2O3 5.17 wt %.

[0091] The digestion temperature of the high-activity lime used in this embodiment is 110° C. and the digestion time is 40 min.

[0092] The components of the fly ash used in this embodiment include: SiO2 49.08 wt%, Al2O3 15.78 wt%, and CaO 9.26 wt%.

[0093] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 4 hours, and then demolded and cured at room temperature to finally obtain a formed self-heating early-strength tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 57.7MPa.

[0094] Example 5 The self-heating early-strength tailings-based polymer of this embodiment is obtained by forming and curing a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 5:1, and the water content of the mixed slurry is 25 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 100 parts of high-calcium tailings, 1 part of sodium hydroxide, 1 part of high-activity lime and 125 parts of fly ash; the raw materials including the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy planetary ball mill with a rotation speed of 1000 rpm and a processing time of 5 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 10:1; the mass ratio of the water reducing agent to the water glass is 0.1:1.

[0095] The water reducing agent used in this embodiment is an aminosulfonic acid water reducing agent.

[0096] The thermal insulation material used in this embodiment is polystyrene particles.

[0097] The components of the high calcium tailings used in this embodiment include: CaO 15.22wt%, SiO2 20.18wt%, Al2O3 5.17wt%.

[0098] The digestion temperature of the high-activity lime used in this embodiment is 100° C. and the digestion time is 30 min.

[0099] The components of the fly ash used in this embodiment include: SiO2 49.08 wt%, Al2O3 15.78 wt%, and CaO 9.26 wt%.

[0100] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 72 hours. After demolding, it is cured at room temperature to finally obtain a formed self-heating early-strength tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 56.4MPa.

[0101] It can be seen from the above examples that the geopolymers prepared in the present invention have good compressive strength, and the compressive strength grades are all above 42.5R, and most of them meet the 52.5R grade. It can be seen from the examples that the geopolymer of the present invention can be cured at room temperature, and the compressive strength can reach a higher standard in 7 days. Compared with the prior art geopolymers that need to be cured under high temperature conditions, the geopolymer of the present invention has obvious advantages.

[0102] Comparative Example 1 Compared with Example 1, this comparative example uses ordinary ball milling to replace high-energy ball milling, and other processes are consistent with Example 1. The specific details are as follows.

[0103] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 40:1, and the water content of the mixed slurry is 20 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 100 parts of high calcium tailings, 2 parts of sodium hydroxide, 5 parts of high active lime and 100 parts of fly ash; firstly, the high calcium tailings, sodium hydroxide and high active lime are ground by an ordinary ball mill (rotation speed is 500 rpm, processing time is 20 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 3:1; the mass ratio of the water reducing agent to the water glass is 0.4:1.

[0104] The water reducing agent used in this comparative example is a polycarboxylic acid water reducing agent.

[0105] The thermal insulation material used in this comparative example is polystyrene particles.

[0106] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0107] The digestion temperature of the high-activity lime used in this comparative example is 90°C and the digestion time is 60 minutes.

[0108] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0109] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 24 hours. After demolding, it is cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 24.2MPa.

[0110] The high calcium tailings treated by high energy ball mill and ordinary ball mill in Example 1, Example 2 and Comparative Example 1 were subjected to XRD test. The results are as follows: Figure 1 It can be found that the main mineral components in the high calcium tailings are quartz, biotite, chlorite, phillipsite, albite, etc. The diffraction peak intensities of biotite, chlorite, phillipsite and albite in the high calcium tailings after mechanical activation in Examples 1 and 2 are significantly weakened or even disappear compared to the tailings after ordinary ball milling in Comparative Example 1, which indicates that after mechanical activation, the high calcium tailings are initially transformed from a crystalline state to an amorphous state.

[0111] The difference between high-energy ball milling and ordinary ball milling mainly lies in the difference in machine structure design and output energy. An ordinary ball mill is usually a rotating cylinder filled with grinding media and materials to be ground, and is not specially designed for high energy input. Ordinary ball mills are mainly used for crushing particles, mixing materials and homogenizing particle size distribution. They usually do not cause significant physical and chemical changes and are mainly used to refine particles without changing the intrinsic structure of the material. The characteristic of high-energy ball milling is that it can achieve higher rotation speeds and stronger impact forces in its design, making the collision between the grinding media and the material more intense, thereby introducing more energy. In the embodiment of the present invention, a large amount of mechanical energy is applied in a short period of time through the rapid rotation or vibration of the high-energy ball mill, so that it can cooperate with sodium hydroxide to promote the material to complete the transformation from crystalline to amorphous state.

[0112] Comparative Example 2 Compared with Example 2, this comparative example uses low-activity lime to replace high-activity lime, and other processes are consistent with Example 2. The specific details are as follows.

[0113] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 10 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 100 parts of high-calcium tailings, 2 parts of sodium hydroxide, 2.5 parts of low-activity lime and 50 parts of fly ash; the high-calcium tailings, sodium hydroxide and low-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 600 rpm and a processing time of 30 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 5:1; the mass ratio of the water reducing agent to the water glass is 0.1:1.

[0114] The water reducing agent used in this comparative example is a lignin sulfonate water reducing agent.

[0115] The thermal insulation material used in this comparative example is vitrified microspheres.

[0116] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0117] The digestion temperature of the low-activity lime used in this comparative example is 60°C and the digestion time is 12 min.

[0118] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0119] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 48 hours. After demolding, it is cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 41.35 MPa.

[0120] The geopolymers obtained in Example 2 and Comparative Example 2 were subjected to FTIR analysis. The results are as follows: Figure 2 As shown. Example 2 uses high-activity lime, while Comparative Example 2 uses low-activity lime. As can be seen from the figure, the shapes of the two graphs are similar, indicating that although the addition of high-activity lime will affect the rate of geopolymer hydration reaction and compressive strength relative to low-activity lime, the product composition is basically the same. -1 and 1642cm -1 The stretching and bending vibration peaks of -OH at 1444 cm-1 Nearby is the stretching vibration peak of CO, which may be due to the CO2 in the air entering the alkaline slurry to generate CO3 2- , 561cm -1 and 455cm -1 The vibration peaks corresponding to Al-O and Si-O bonds are 1011 cm -1 The corresponding Si-O-Al (Si) vibration peak of geopolymer NASH gel, compared with low-activity lime, after adding high-activity lime, the wave number here moves to the low band, indicating that SiO4 tetrahedron is replaced by more AlO4 tetrahedron, the degree of geopolymer polymerization increases, more gel phase is produced, and the compressive strength of geopolymer is improved. However, the digestion temperature of ordinary quicklime is low, the digestion time is short, it is difficult to provide enough heat, and the duration is not enough to improve the strength of geopolymer.

[0121] Comparative Example 3 Compared with Example 2, this comparative example reduces the amount of high-activity lime (the mass ratio of high-calcium tailings to high-activity lime is 120:1), and other processes are consistent with Example 2, and the specific details are as follows.

[0122] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 10 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 300 parts of high-calcium tailings, 6 parts of sodium hydroxide, 2.5 parts of high-activity lime and 150 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 600 rpm and a processing time of 30 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 5:1; the mass ratio of the water reducing agent to the water glass is 0.1:1.

[0123] The water reducing agent used in this comparative example is a lignin sulfonate water reducing agent.

[0124] The thermal insulation material used in this comparative example is vitrified microspheres.

[0125] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0126] The digestion temperature of the high-activity lime used in this comparative example is 100°C and the digestion time is 50 minutes.

[0127] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0128] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 48 hours. After demolding, it is cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 39.85MPa.

[0129] Comparative Example 4 Compared with Example 2, the comparative example increases the amount of high-activity lime (the mass ratio of high-calcium tailings to high-activity lime is 5:1), and the other processes are consistent with Example 2, and the specific details are as follows.

[0130] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 10 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 100 parts of high-calcium tailings, 2 parts of sodium hydroxide, 20 parts of high-activity lime and 50 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 600 rpm and a processing time of 30 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 5:1; the mass ratio of the water reducing agent to the water glass is 0.1:1.

[0131] The water reducing agent used in this comparative example is a lignin sulfonate water reducing agent.

[0132] The thermal insulation material used in this comparative example is vitrified microspheres.

[0133] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0134] The digestion temperature of the high-activity lime used in this comparative example is 100°C and the digestion time is 50 minutes.

[0135] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0136] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 48 hours. After demolding, it is cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 54.2MPa.

[0137] Comparative analysis of different high calcium tailings and high active lime dosage ratios in Example 2, Comparative Examples 3 and 4 shows that the strength of the geopolymer obtained in Comparative Example 3 is relatively low. Based on the experimental phenomenon, it is speculated that the relatively high high calcium tailings and high active lime dosage ratio is insufficient to generate sufficient heat, which has limited promoting effect on the polymerization reaction of active silicon aluminum calcium components in high calcium tailings and fly ash and geopolymer additive B; the product obtained in Comparative Example 4 has higher strength, but more high active lime will reduce the acid resistance and chemical corrosion resistance of the geopolymer, and at the same time increase the material cost, as well as environmental problems and safety hazards.

[0138] Comparative Example 5 Compared with Example 3, this comparative example only performs mechanical activation on the high-calcium tailings, and the other processes are consistent with Example 3. The specific details are as follows.

[0139] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 50:1, and the water content of the mixed slurry is 30 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 1 part of sodium hydroxide, 1 part of highly active lime and 40 parts of fly ash; the high-calcium tailings are first mechanically activated by high-energy ball milling (using a high-energy planetary ball mill with a rotation speed of 800 rpm and a processing time of 20 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 3:1; the mass ratio of the water reducing agent to the water glass is 0.3:1.

[0140] The water reducing agent used in this comparative example is a polycarboxylic acid water reducing agent.

[0141] The thermal insulation material used in this comparative example is composite silicate.

[0142] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0143] The digestion temperature of the high-activity lime used in this comparative example is 120°C and the digestion time is 30 minutes.

[0144] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0145] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 40 hours, and then demolded and cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 37.35MPa.

[0146] Comparative Example 6 Compared with Example 3, this comparative example changes to mechanically activate the high-calcium tailings, sodium hydroxide, and high-activity lime separately, and the other processes are consistent with Example 3. The specific details are as follows.

[0147] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 50:1, and the water content of the mixed slurry is 30 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 1 part of sodium hydroxide, 1 part of high-activity lime and 40 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are firstly mechanically activated by high-energy ball milling (using a high-energy planetary ball mill with a rotation speed of 800 rpm and a processing time of 20 minutes), and then all the raw materials of the geopolymer precursor powder A are uniformly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 3:1; the mass ratio of the water reducing agent to the water glass is 0.3:1.

[0148] The water reducing agent used in this comparative example is a polycarboxylic acid water reducing agent.

[0149] The thermal insulation material used in this comparative example is composite silicate.

[0150] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0151] The digestion temperature of the high-activity lime used in this comparative example is 120°C and the digestion time is 30 minutes.

[0152] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0153] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 40 hours, and then demolded and cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 40.5MPa.

[0154] Comparing Example 3 with Comparative Examples 5 and 6, it is found that the effects of activating high-calcium tailings alone, or activating high-calcium tailings, sodium hydroxide and high-activity lime separately are obviously inferior to the effect of grinding the three together, which shows the importance of grinding high-calcium tailings together with sodium hydroxide and high-activity lime; high-energy ball milling synergizes with sodium hydroxide to promote the formation of gels such as CSH and NASH, thereby enhancing the compressive strength of geopolymers; at the same time, the use of high-activity lime can greatly increase the heat released during the hydration process of geopolymers, and the use of sodium hydroxide dissolution to further supplement the heat is conducive to the geopolymerization reaction and hydration reaction.

[0155] Comparative Example 7 Compared with Example 3, this comparative example does not use sodium hydroxide, and other processes are consistent with Example 3, and the specific details are as follows.

[0156] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 50:1, and the water content of the mixed slurry is 30 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 1 part of high-activity lime and 40 parts of fly ash; the high-calcium tailings and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy planetary ball mill with a rotation speed of 800 rpm and a processing time of 20 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 3:1; the mass ratio of the water reducing agent to the water glass is 0.3:1.

[0157] The water reducing agent used in this comparative example is a polycarboxylic acid water reducing agent.

[0158] The thermal insulation material used in this comparative example is composite silicate.

[0159] The components of the high calcium tailings used in this comparative example include: CaO 29.88wt%, SiO2 49.95wt%, Al2O3 9.13wt%.

[0160] The digestion temperature of the high-activity lime used in this comparative example is 120°C and the digestion time is 30 minutes.

[0161] The components of the fly ash used in this comparative example include: SiO2 35.23 wt%, Al2O3 30.65 wt%, and CaO 2.65 wt%.

[0162] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 40 hours. After demolding, it is cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 39.5MPa.

[0163] Comparing Example 3 with Comparative Example 7, it is found that the compressive strength of the geopolymer obtained without adding sodium hydroxide is significantly lower. It is speculated that the high-energy ball mill grinds the high-calcium tailings and sodium hydroxide powder together, which can not only refine the particle size of the high-calcium tailings and increase the specific surface area, but also the strong alkaline environment provided by sodium hydroxide can promote micro-reactions on the surface of the high-calcium tailings, and cooperate with high-energy ball milling to transform the silicon, aluminum and calcium components in the high-calcium tailings into a more reactive amorphous state. In addition, it can also release heat to provide heat protection for the self-heating early strength geopolymer, thereby promoting the improvement of the strength of the geopolymer.

[0164] Comparative Example 8 Compared with Example 4, the amount of sodium hydroxide used in this comparative example is increased (the mass ratio of high-calcium tailings to sodium hydroxide is 10:1), and the other processes are consistent with Example 4, and the specific details are as follows.

[0165] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 15 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 6 parts of sodium hydroxide, 3 parts of high-activity lime and 20 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 200 rpm and a processing time of 60 minutes), and then all the raw materials of the geopolymer precursor powder A are mixed uniformly by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 1:1; the mass ratio of the water reducing agent to the water glass is 0.2:1.

[0166] The water reducing agent used in this comparative example is an aminosulfonic acid water reducing agent.

[0167] The thermal insulation material used in this comparative example is composite silicate.

[0168] The components of the high calcium tailings used in this comparative example include: CaO 15.22 wt %, SiO2 20.18 wt %, Al2O3 5.17 wt %.

[0169] The digestion temperature of the high-activity lime used in this comparative example is 110°C and the digestion time is 40 minutes.

[0170] The components of the fly ash used in this comparative example include: SiO2 49.08 wt%, Al2O3 15.78 wt%, and CaO 9.26 wt%.

[0171] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 4 hours, and then demolded and cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 41.8MPa.

[0172] Comparative Example 9 Compared with Example 4, the amount of sodium hydroxide used in this comparative example is reduced (the mass ratio of high-calcium tailings to sodium hydroxide is 120:1), and the other processes are consistent with Example 4, and the specific details are as follows.

[0173] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 15 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 0.5 parts of sodium hydroxide, 3 parts of high-activity lime and 20 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 200 rpm and a processing time of 60 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 1:1; the mass ratio of the water reducing agent to the water glass is 0.2:1.

[0174] The water reducing agent used in this comparative example is an aminosulfonic acid water reducing agent.

[0175] The thermal insulation material used in this comparative example is composite silicate.

[0176] The components of the high calcium tailings used in this comparative example include: CaO 15.22 wt %, SiO2 20.18 wt %, Al2O3 5.17 wt %.

[0177] The digestion temperature of the high-activity lime used in this comparative example is 110°C and the digestion time is 40 minutes.

[0178] The components of the fly ash used in this comparative example include: SiO2 49.08 wt%, Al2O3 15.78 wt%, and CaO 9.26 wt%.

[0179] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 4 hours, and then demolded and cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 43.5MPa.

[0180] Combined with the experimental phenomena, Example 4 is compared with Comparative Examples 8 and 9. It is found that when the content of sodium hydroxide is too low, it is not enough to induce micro-reactions on the surface of high-calcium tailings, and the heat provided is also insufficient. In addition, the alkalinity in the reaction system is reduced, which may also cause the Si and Al in some tailings and fly ash to be unable to be fully dissolved, and the gel material of the geopolymer is reduced, resulting in a decrease in the compressive strength of the sample. Excessive alkali may introduce more pores, resulting in a decrease in the density of the geopolymer and an increase in the water absorption rate, reducing the mechanical properties and durability of the geopolymer, and subsequently the geopolymer will produce a large amount of white frost during the placement process.

[0181] Comparative Example 10 Compared with Example 4, the amount of fly ash used in this comparative example is increased (the mass ratio of high calcium tailings to fly ash is 0.6:1), and the other processes are consistent with Example 4, and the specific details are as follows.

[0182] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 15 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 2 parts of sodium hydroxide, 3 parts of high-activity lime and 100 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 200 rpm and a processing time of 60 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 1:1; the mass ratio of the water reducing agent to the water glass is 0.2:1.

[0183] The water reducing agent used in this comparative example is an aminosulfonic acid water reducing agent.

[0184] The thermal insulation material used in this comparative example is composite silicate.

[0185] The components of the high calcium tailings used in this comparative example include: CaO 15.22 wt %, SiO2 20.18 wt %, Al2O3 5.17 wt %.

[0186] The digestion temperature of the high-activity lime used in this comparative example is 110°C and the digestion time is 40 minutes.

[0187] The components of the fly ash used in this comparative example include: SiO2 49.08 wt%, Al2O3 15.78 wt%, and CaO 9.26 wt%.

[0188] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 4 hours, and then demolded and cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 53.8MPa.

[0189] Comparative Example 11 Compared with Example 4, this comparative example reduces the amount of fly ash used (the mass ratio of high calcium tailings to fly ash is 5:1), and other processes are consistent with Example 4, and the specific details are as follows.

[0190] The tailings-based polymer in this comparative example is obtained by forming and solidifying a slurry formed by mixing a geopolymer precursor powder A and a geopolymer additive B with water; the mass ratio of the geopolymer precursor powder A and the geopolymer additive B is 30:1, and the water content of the mixed slurry is 15 wt%; The raw materials of the geopolymer precursor powder A include (by weight): 60 parts of high-calcium tailings, 2 parts of sodium hydroxide, 3 parts of high-activity lime and 12 parts of fly ash; the high-calcium tailings, sodium hydroxide and high-activity lime are first mechanically activated by high-energy ball milling (using a high-energy stirring ball mill with a rotation speed of 200 rpm and a processing time of 60 minutes), and then all the raw materials of the geopolymer precursor powder A are evenly mixed by ordinary ball milling; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass, which are uniformly mixed to obtain the geopolymer additive B. The mass ratio of the water reducing agent to the thermal insulation material is 1:1; the mass ratio of the water reducing agent to the water glass is 0.2:1.

[0191] The water reducing agent used in this comparative example is an aminosulfonic acid water reducing agent.

[0192] The thermal insulation material used in this comparative example is composite silicate.

[0193] The components of the high calcium tailings used in this comparative example include: CaO 15.22 wt %, SiO2 20.18 wt %, Al2O3 5.17 wt %.

[0194] The digestion temperature of the high-activity lime used in this comparative example is 110°C and the digestion time is 40 minutes.

[0195] The components of the fly ash used in this comparative example include: SiO2 49.08 wt%, Al2O3 15.78 wt%, and CaO 9.26 wt%.

[0196] When the slurry is being formed and solidified, it is first cast in a prefabricated mold, then covered with a film and solidified at room temperature for 4 hours, and then demolded and cured at room temperature to finally obtain a formed tailings-based polymer. After testing, the 7-day compressive strength value of the obtained geopolymer is 40.25MPa.

[0197] By comparing Example 4 with Comparative Examples 10 and 11, it is found that when the tailings dosage is too high, the compressive strength of the geopolymer is reduced. It is speculated that this is because the active silicon and aluminum components in the raw materials are reduced, which is not conducive to the subsequent hydration reaction of the geopolymer. When the amount of tailings is small, the compressive strength of the prepared geopolymer does not change much, but the consumption of tailings is reduced, which is not conducive to the digestion of tailings.

[0198] Table 1 Compressive strength test results of various embodiments and comparative examples

Claims

1. A self-heating early-strength tailings-based polymer, characterized in that: The slurry is formed by mixing the geopolymer precursor powder A and the geopolymer additive B with or without water, and then formed and solidified; The raw materials of the geopolymer precursor powder A include high calcium tailings, sodium hydroxide, high active lime and fly ash; before mixing the raw materials of the geopolymer precursor powder A, the raw materials including the high calcium tailings, sodium hydroxide and high active lime are mechanically activated together; The raw materials of the geopolymer additive B include water reducing agent, thermal insulation material and water glass; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to high active lime is 10-110:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to sodium hydroxide is 20-110:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is less than 4.5:1; In the slurry, the mass ratio of the geopolymer precursor powder A to the geopolymer additive B is 1-100:1; The water content of the slurry is below 40 wt %.

2. The self-heating early-strength tailings-based polymer according to claim 1, characterized in that: The mechanical force activation adopts a high-energy ball milling method.

3. The self-heating early-strength tailings-based polymer according to claim 1, characterized in that: The water reducer is one or more of polycarboxylic acids, lignin sulfonates, and aminosulfonic acids; the thermal insulation material is one or more of polystyrene particles, glass beads, and composite silicates; and the water content of the water glass is 50 wt% to 60 wt%.

4. The self-heating early-strength tailings-based polymer according to claim 2, characterized in that: The rotation speed of the high-energy ball milling method is above 200 rpm; the processing time of the high-energy ball milling method is above 5 minutes.

5. The self-heating early-strength tailings-based polymer according to claim 1, characterized in that: The components of the high-calcium tailings include: CaO 15 wt%~30 wt%, SiO2 20 wt%~50 wt%, Al2O3 5 wt%~10 wt%; the digestion temperature of the high-activity lime is above 90°C, and the digestion time is more than 30 minutes.

6. The self-heating early-strength tailings-based polymer according to claim 1 or 5, characterized in that: In the geopolymer precursor powder A, the mass ratio of high calcium tailings to high active lime is 20-100:1; in the geopolymer precursor powder A, the mass ratio of high calcium tailings to sodium hydroxide is 30-100:1; In the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is less than 4:1; The fly ash comprises: SiO2 35 wt%~50 wt%, Al2O3 15 wt%~35wt%, CaO 2 wt%~10 wt%.

7. The self-heating early-strength tailings-based polymer according to claim 6, characterized in that: In the geopolymer precursor powder A, the mass ratio of high calcium tailings to fly ash is 0.8-3:

1.

8. The self-heating early-strength tailings-based polymer according to claim 1 or 3, characterized in that: In the geopolymer additive B, the mass ratio of the water reducing agent to the thermal insulation material is 1-10:

1.

9. The self-heating early-strength tailings-based polymer according to claim 1 or 3, characterized in that: In the geopolymer additive B, the mass ratio of the water reducer to the water glass is 0.1-0.4:

1.

10. The self-heating early-strength tailings-based polymer according to claim 1, characterized in that: In the slurry, the mass ratio of the geopolymer precursor powder A to the geopolymer additive B is 2-60:1; the water content of the slurry is 10 wt%-30 wt%; and the curing time of the slurry is 4-72 h.

Citation Information

Patent Citations

  • Concrete using granite powder as major mineral admixture

    CN104844081A

  • Method for preparing integrated cementing material by using granite stone powder and fire coal slag

    CN113620618A

  • Activated coal cinder and method for preparing hydraulic cementing material by using activated coal cinder

    CN113735473A

  • Geopolymer cementing material based on multiple solid wastes and preparation method thereof

    CN115849781A

  • Heat-conducting geopolymer composite material as well as preparation and application thereof

    CN111393056A